Solitary Breast Cancer Metastasis to the Esophagus – a Multimodal Diagnostic Approach - Talanow, R.; Vieweg, H.; Andresen, R. (Zeitschrift für Gastroenterologie, 2013)
We present a case of late breast cancer metastasis over 15 years since the initial diagnosis which was highly unusual because of its solitary aspect with no other evidence of the disease and its uncommon localization in the esophagus. With a history of breast cancer, several differential diagnoses for suspicious space-occupying masses need to be considered, like radiation-induced cancer or multiple neoplasm. A multimodal diagnostic approach can lead to the correct diagnosis. Endoscopy, endoscopic ultrasound (EUS) including EUS-guided fine-needle aspiration (FNA), CT and PET/CT findings are provided.
Keywords: breast cancer; esophageal metastasis; PET/CT